Efficacy of Tranexamic Acid in Combination With Conventional Therapy for Treatment of Pph (Journal of Chittagong Medical College Teachers' Association, 2016)
Haemorrhage is the leading cause of maternal mortality, accounting for about 35% of all maternal deaths. About 14 million women around the world suffer from Post Partum Hemorrhage (PPH) every year. Of them, about 2% die with an average interval of 2-4 hrs from onset of bleeding. Tranexamic Acid (TXA) is the most effective of the available anti-fibrinolytics, which has been shown to be very useful in reducing blood loss and incidence of blood transfusion in different surgeries. The study was done to see the efficacy of injectable tranexamic acid in addition to conventional treatment in control of atonic PPH. In this study, women having atonic PPH following vaginal delivery were grouped into two, A & B. Group A received 2 amp inj.TXA (Tranexamic acid) i.v immediately after diagnosis of PPH and Group B received 10ml distilled water i.v. Both groups received all other necessary measures for control of PPH and outcomes were recorded in a preformed data collection sheet. All data were analyzed by computer based software Statistical Packages for Social Science (SPSS) version 15.The results showed that tranexamic acid significantly reduced the volume of blood loss in atonic PPH, 1141.23±489.91 ml in study group versus 1365.25±428.22 ml in control group.PPH control within 2 hr with medical therapies occurred more in TXA group (88.09%) than in control group (57.14%). Invasive procedures were less required in TXA group than in control group ,condom catheter in 4 pt. (9.52%) compared to 11(26.19%) in control group. Hysterectomy was done in 1 case of TXA group compared to 7 cases of control group. TXA also significantly reduced the necessity of blood transfusion in PPH, 26.19% in TXA group compared to 54.76% in control group. So one gm i.v. tranexamic acid given along with other conventional measures at the diagnosis of atonic PPH significantly reduces the amount of blood loss, requirement of blood transfusion, necessity of invasive procedures.  JCMCTA 2015 ; 26 (2) : 34 - 39